Cartographic expeditions and visual culture in the nineteenth-century Americas - Capello, Ernesto; Rosenbaum, Julia B. (New York, NY : Routledge Taylor & Francis Group, 2021)
"During the nineteenth century, gridding, graphing and surveying proliferated as never before as nations and empires expanded into hitherto "unknown" territories. Though nominally geared toward justifying territorial claims and collecting scientific data, expeditions also produced vast troves of visual and artistic material. This book considers the explosion of expeditionary mapping and its links to visual culture across the Americas, arguing that acts of measurement are also aesthetic acts. Such visual interventions intersect with new technologies, with sociopolitical power and conflict, and with shifting public tastes and consumption practices. Several key questions shape this examination: What kinds of nineteenth-century visual practices and technologies of seeing do these materials engage? How does scientific knowledge get translated into the visual and disseminated to the public? What are the commonalities and distinctions in mapping strategies between North and South America? How does the constitution of these lines reorder space and the natural landscape itself? The volume represents the first transnational and hemispheric analysis of nineteenth-century cartographic aesthetics, and features the multi-disciplinary perspective of historians, geographers, and art historians"--
Introduction: The expeditionary impulse / Ernesto Capello and Julia B. Rosenbaum -- Section 1. Seeing and Not Seeing. Alexander von Humboldt: The aesthetic science of landscape pictures / Alicia Lubowski-Jahn -- Triangulating the view: Art and the great surveys of the American West in the 1870s / Joni L. Kinsey -- Cartographic representation in the Age of Vernacular Landscape: Pictorial metaphor in Stephen Long's map of the country drained by the Mississippi (1822) / Kenneth Haltman -- Seeing solitary deserts full of people: The Chorographic Commission in Colombia's Eastern Plains, 1856 / Nancy P. Appelbaum -- Section 2. Lines and Tracings. Intervisible border: Photographs and monuments along the US-Mexico boundary / Katherine G. Morrissey -- "Visual Expeditions" supporting geopolitical vindications: Maps, photographs and other visual devices in the diplomatic dispute over the Andes as a natural border (1900) / Carla Lois -- Female eyes on South America: Maria Graham in Brazil / Katherine Manthorne -- Science, wonder, and tourism in the early mapping of Yellowstone National Park / James R. Akerman -- Section 3. Art and the Expeditionary Impulse. Delineating land: Art, mapping, and the work of Frederic Edwin Church / Julia B. Rosenbaum -- Albert Operti: An Arctic historical painter and the popular sublime / Ernesto Capello.
OCLC-licensed vendor bibliographic record.
Keywords: Cartography -- America -- History -- 19th century; America -- Territorial expansion; HISTORY / General